Availability of, Barriers to Performing, and Educational Practices of Interventional Procedures for Refractory Pain in Cancer Patients: A Nationwide Survey of Designated Cancer Hospitals in Japan - Yoshihisa Matsumoto; Yuko Uehara; Akio Mizushima; Toshifumi Kosugi; Miyuki Sone; Naoki Nakamura; Mitsunori Miyashita; Tatsuya Morita; Takuhiro Yamaguchi; Eriko Satomi (Palliative Medicine Reports)
Background: Because of the limitations of pharmacological therapy, nonpharmacological therapies including intervention procedures are also important for quality of cancer pain management. Objective: To clarify the availability of, number performed, barriers to performing, and educational practices of four interventional procedures (celiac plexus neurolysis/splanchnic nerve neurolysis, phenol saddle block, epidural analgesia, and intrathecal analgesia) in designated cancer hospitals. Design: Cross-sectional survey. Setting: Designated cancer hospitals certified by the Japanese Government. Methods: We administered self-administered questionnaires to collect general information about the facility and interventional procedures for refractory cancer pain between January and April 2021. Results: Questionnaires were sent to 402 facilities, and we received 199 valid responses (49.5%). Regarding availability, 36.7%–59.8% of the designated cancer hospitals reported that each procedure was available. Regarding the frequency of these procedures performed in the past 3 years, medians ranged from 1 to 4 times for each procedure. Among designated cancer hospitals, 44.7–65.8% reported the presence of barriers. Barriers such as “no/few physicians technically able to perform the procedure,” “inability to follow-up after the procedure is implemented,” and “the facilities to which patients may be referred after implementation are limited” were particularly pronounced. Training and treatment practice were provided by 30.7–55.8% of designated cancer hospitals for the procedures. Moreover, 12.6%–15.6% of designated cancer hospitals educated physicians and nurses responsible for cancer care in the region about pain treatment for the procedures. Conclusions: Our findings suggest that designated cancer hospitals need to improve the availability, training, and education of interventional procedures.